Migraine and other headaches in transient ischemic attacks - E. R. Lebedeva; N. M. Gurary; J. Olesen (Неврология, нейропсихиатрия, психосоматика)
Headache is a common symptom in acute cerebrovascular diseases; however, no studies have evaluated the prevalence of specific headache types in patients with transient ischemic attacks (ТIАs).Objective: to analyze all headaches within the last year and the last week before and during ТIАs.Patients and methods. TIA patients included in the study (female 55% (n=120); mean age, 56.1 years) according to the existing definition of TIAs had a transient neurological dysfunction episode caused by focal brain damage or retinal ischemia for up to 24 hours without forming a new acute heart attack on diffusion-weighted MRI (n=112) or CT (n=8). All the patients were examined by one neurologist within one day after their admission. Patients (female 64% (n=192); mean age, 58.7 years) who had been admitted with a diagnosis of lumbago, lumbar spine osteochondrosis, or gastrointestinal ulcer were examined as a control group. A clinical semistructured face-to-face interview with the patients of both groups was carried out to analyze headache.Results and discussion. The prevalence of migraine without aura during one year before TIA was substantially higher in patients with TIA than in control ones: 20.8 and 7.8%, respectively (p=0.002). Twenty-two (18.3%) patients had sentinel or warning headache within the last week before a TIA that manifested as an increase in and greater frequency of previous headache, as lack of effect of painkillers, and as the emergence of a new type of headaches, which were previously absent. During TIAs, 16 (13.3%) patients developed a new type of headache. Twelve of these 16 patients had migraine-like headache; three patients had headache resembling tension headache; one patient had a thunderclap headache. None of the control patients was found to have a new type of headache. TIAs were significantly more common in the vertebrobasilar basin than in the carotid artery one in patients with headache during the last week before and during TIA.Conclusion. The one year prevalence of migraine was significantly higher in ТIА patients than in control patients, and so was the prevalence of headache within the last week before and during TIA. Migraine-like headache prevailed among the new types of headaches in the development of TIA. A previous headache with a change in characteristics and a new type of headache can be predictors for TIA.